Influence of Pathogenic Microorganisms on Spectral Characteristics of Leaf Pigments in Apple Clonal Rootstocks - Maslova, M. V.; Dubrovsky, M. L.; Grosheva, E. V. (Journal of applied spectroscopy, 2025)
Spectral reflectance curves (SRCs) of ethanol extracts of leaf pigments concentrated on filter paper were analyzed. The areas of the spectrum that were the most subject to change in the process of pathogenesis were identified. A change in the slope of the SRC was noted in the area connecting the point of maximum absorption of the studied pigment and the nearest point that was not related to its content. The range 510−590 nm was informative for the analysis of carotenoids in apple rootstock forms; 640−670 nm and 670−700 nm, for chlorophyll. The angular coefficients in the equations of the trend lines in different genotypes changed in the studied SRC sectors (k 510–590 , k 640–670 , and k 670–700 ) depending on the resistance of the host plant's pigment apparatus to the parasite. The forms that showed the greatest resistance to the complex of pathogenic micromycetes and to the bacterium P. syringae were identified.